Could Positive Feedback Enable Bacterial Pheromone Signaling To Coordinate Behaviors in Response to Heterogeneous Environmental Cues? - Eric V. Stabb (American Society for Microbiology, 2018)
ABSTRACT Pheromone signaling (PS) underlies many important bacterial behaviors, yet its ecological functions remain unresolved. Because pheromone-mediated behaviors require high cell density, the term “quorum sensing” is widely used to describe and make sense of PS. However, while this term has unified and popularized the field, bacterial PS clearly has roles beyond census taking, and the complexities of PS circuits indicate broader functional capacities. Two common features of bacterial PS are its regulation in response to environmental conditions and positive-feedback loops. Combined, these could enable PS to coordinate quorum-dependent group behaviors in response to heterogeneous environmental cues. Particularly in PS systems where positive feedback is strong, cells that are relatively far from a stimulatory environment could be recruited to a group response. Testing this model will benefit from in situ examination of relevant environmental cues and PS outputs in cells across populations, with and without positive feedback, in heterogeneous environments.